Databases and School Libraries (Journal of human and social sciences, 2015)
This study aims to propose a design for an integrated database for the school library to enable it to play a more effective role in the educational process. The paper discusses the declining role of the school library in light of contemporary cultural and social challenges and proposes transforming it from a mere book repository into an active information center and a cultural actor within the school and the local community. The research provides a detailed model for the database, including tables for students, classes, teachers, courses, schedules, and library holdings, explaining the relationships between them and the expected outputs. The study concludes that implementing such a system can contribute to rationalizing educational decisions and increasing the effectiveness of educational performance.
Keywords: Databases; School Libraries; Information Technology; School Administration; Education